Air pollution research: visualization of research activity using density-equalizing mapping and scientometric benchmarking procedures - Zell, Hanna (BioMed Central, 2010)
BACKGROUND: Due to constantly rising air pollution levels as well as an increasing awareness of the hazardousness of air pollutants, new laws and rules have recently been passed. Although there has been a large amount of research on this topic, bibliometric data is still to be collected. Thus this study provides a scientometric approach to the material published on this subject so far. METHODS: For this purpose, data retrieved from the "Web of Science" provided by the Thomson Scientific Institute was analyzed and visualized both with density-equalizing methods and classic data-processing methods such as tables and charts. RESULTS: For the time span between 1955 and 2006, 26,253 items were listed and related to the topic of air pollution, published by 124 countries in 24 different languages. General citation activity has been constantly increasing since the beginning of the examined period. However, beginning with the year 1991, citation levels have been rising exponentially each year, reaching 39,220 citations in the year 2006. The United States, the UK and Germany were the three most productive countries in the area, with English and German ranked first and second in publishing languages, followed by French. An article published by Dockery, Pope, Xu et al. was both the most cited in total numbers and in average citation rate. J. Schwartz was able to claim the highest total number of citations on his publications, while D.W. Dockery has the highest citation rate per publication. As to the subject areas the items are assigned with, the most item were published in Environmental Sciences, followed by Meteorology & Atmospheric Sciences and Public, Environmental & Occupational Health. Nine out of the ten publishing journals with more than 300 entries dealt with environmental interests and one dealt with epidemiology. CONCLUSIONS: Using the method of density-equalizing mapping and further common data processing procedures, it can be concluded that scientific work concerning air pollution and related topics enjoys unbrokenly growing scientific interest. This can be observed both in publication numbers and in citation activity.